7.3: Depletion‐Mode Oxide‐TFT Shift Register with Wide Operating Frequency Range for AMOLED Displays. Issue 1 (June 2015) - Han, Inhyo; Song, Eunji; Kang, Byeonguk; Oh, Kilhwan; Kim, Bumsik; Oh, Changho; Ahn, Byungchul; Nam, Hyoungsik
Abstract : This paper proposed a shift register circuit for GIP (Gate driver In Panel) in active matrix organic light emitting diode displays which enable cost innovation and narrow bezel. The shift register circuit which is made up with depletion mode oxide TFTs is designed to be driven at low operation frequency for power reduction in still image as well as to be driven at high operation frequency for motion picture quality improvement in moving image. However, it is especially difficult to operate at low frequency because oxide TFTs easily have negative Vth and zero gate‐source voltage turns out to be unable to shut down current path. The proposed shift register is integrated in a 15‐inch HD (1366 × 768, 105ppi) AMOLED panel, it is ensured that the shift register have wide operating frequency range from 1Hz to 240 Hz. In Addition, it is verified that the panel operates at high temperature(60°C) during 1, 000 hours without any problems.